The Nyama (kinship) Documentary as an Intolerant Comparative Discourse in Pegayaman Village, Buleleng, Bali - I Komang Arba Wirawan; I Gede Arya Sugiartha (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2020)
The Nyama documentary is as a counter-discourse on intolerant attitudes in Indonesia. Nyama film was the result of research and creation of written and audio-visual data documentation of the acculturation of art and culture in the Muslim village of Pegayaman Buleleng, Bali. It was an observational/direct cinema-style documentary film acculturation of Hindu and Islamic arts and culture in Pegayaman Village, Buleleng, Bali. The Nyama film identified the perceptions and acculturation of art and culture in Pegayaman Village, Buleleng, Bali. It was a qualitative descriptive research method. Sources of data obtained through a purposive sampling method were done by accidental sampling technique. The location of the sampling was carried out in Pegayaman Village, Buleleng, Bali. The method used in achieving these goals was Representing reality. The documentary tells an event or reality (facts and data). Principally, documentary films are based on facts and are demanded to be loyal to those facts. Discussion of research and creation of this movie is the observational/direct cinema documentaries. This film tells the story of several people in Pegayaman Village. The subjects in this film are not in the same condition but are equally struggling to preserve the acculturation of Hindu and Islamic arts and culture in the Bali region. The information building in this film was a combination of interviews with selected subjects. The results of the research and creation were in the form of Nyama documentary films. The Nyama documentary is an acculturation campaign for arts and culture and a counter-discourse on the intolerant attitude of Indonesian society that is multicultural and has the character of Indonesian nationality.